1998
DOI: 10.1021/bi972131r
|View full text |Cite
|
Sign up to set email alerts
|

ATP-Dependent Human Erythrocyte Glutathione-Conjugate Transporter. II. Functional Reconstitution of Transport Activity

Abstract: Purified dinitrophenyl S-glutathione (DNP-SG) ATPase was reconstituted into artificial liposomes prepared from soybean asolectin. Electron micrography confirmed the formation of unilamellar vesicles with an average radius of 0.25 micron. Intravesicular volume estimated by incorporation of radiolabled inulin into the vesicles was found to be 19.7 +/- 1.3 microL/mL reconstitution solution. Accumulation of the glutathione-conjugate of CDNB, DNP-SG, and of doxorubicin (DOX) in the proteoliposomes was increased in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(84 citation statements)
references
References 22 publications
(35 reference statements)
2
82
0
Order By: Relevance
“…Surprisingly, DNP-SG ATPase-mediated ATP hydrolysis was stimulated not only by the organic anions (e.g., DNP-SG), but also by weak cations such as doxorubicin (DOX) and its metabolites (Awasthi et al, 1994(Awasthi et al, , 1998b. Furthermore, our studies with membrane vesicles (Awasthi et al, 1994) as well as with reconstituted proteoliposomes (Awasthi et al, 1998a) demonstrated that DNP-SG ATPase catalyzed transport of anionic GSH conjugates as well as of weakly cationic drugs such as DOX and colchicine (Awasthi et al, 1994;1998a,b;. ATPdependent transport of both DNP-SG and DOX against a concentration gradient was demonstrated in proteoliposomes reconstituted with highly purified DNP-SG ATPase (Awasthi et al, 1998a).…”
Section: Dnp-sg Atpase a Transporter For Anionic As Well As Cationicmentioning
confidence: 78%
See 2 more Smart Citations
“…Surprisingly, DNP-SG ATPase-mediated ATP hydrolysis was stimulated not only by the organic anions (e.g., DNP-SG), but also by weak cations such as doxorubicin (DOX) and its metabolites (Awasthi et al, 1994(Awasthi et al, , 1998b. Furthermore, our studies with membrane vesicles (Awasthi et al, 1994) as well as with reconstituted proteoliposomes (Awasthi et al, 1998a) demonstrated that DNP-SG ATPase catalyzed transport of anionic GSH conjugates as well as of weakly cationic drugs such as DOX and colchicine (Awasthi et al, 1994;1998a,b;. ATPdependent transport of both DNP-SG and DOX against a concentration gradient was demonstrated in proteoliposomes reconstituted with highly purified DNP-SG ATPase (Awasthi et al, 1998a).…”
Section: Dnp-sg Atpase a Transporter For Anionic As Well As Cationicmentioning
confidence: 78%
“…Furthermore, our studies with membrane vesicles (Awasthi et al, 1994) as well as with reconstituted proteoliposomes (Awasthi et al, 1998a) demonstrated that DNP-SG ATPase catalyzed transport of anionic GSH conjugates as well as of weakly cationic drugs such as DOX and colchicine (Awasthi et al, 1994;1998a,b;. ATPdependent transport of both DNP-SG and DOX against a concentration gradient was demonstrated in proteoliposomes reconstituted with highly purified DNP-SG ATPase (Awasthi et al, 1998a). The transport was temperature-dependent and sensitive to the osmolarity of the assay medium.…”
Section: Dnp-sg Atpase a Transporter For Anionic As Well As Cationicmentioning
confidence: 79%
See 1 more Smart Citation
“…Liposome formation was initiated by the addition of SM2 Biobeads (200 mg/ml). We have shown that vesiculation is complete within 4 h and yields primarily unilammelar vesicles with a median diameter of 0.25 m and intravesicular/extravesicular volume ratio of 18 l/ml (8,22). The liposomes reconstituted with purified recombinant Hsf-1, POB1, and Ralbp1 proteoliposomes were used for delivery of these proteins to cells in culture.…”
Section: Prokaryotic Expression and Purification Of Pob1 And Pob1-(1-mentioning
confidence: 99%
“…We cloned RLIP76 independently, in the search for glutathione-electrophile conjugates (GS-Es) and chemotherapy drug transporters, from a human bone-marrow cDNA library using polyclonal antibodies raised against purified human erythrocyte putative membrane transporter, DNPSG-ATPase (28)(29)(30). The identity of RLIP76 with DNPSG-ATPase was demonstrated by showing that both the human and recombinant protein could be purified by the same GS-E affinity chromatography method (9,(28)(29)(30). Tissue-purified and recombinant RLIP76 have demonstrated constitutive ATPase activity that was stimulated by anionic (e.g., DNP-SG, GS-HNE,) as well as cationic (e.g., DOX) ligands (9,31).…”
Section: Rlip76: a Non-abc Transportermentioning
confidence: 99%